Mães em situação de violência doméstica: fragmentos da clínica - Hebert Geraldo de Souza (2016)
This work is the result of a practice performed in the Attendance Center "Risoleta Neves"(CERNA/MG), human rights institution, part of the structure of the State of Minas Gerais, which conducts psychosocial care for women in situations of domestic violence. So in this scenery of attendance to women, a new configuration of violence aroused interest for research: domestic violence: children against mothers. Faced with this problem, following a psychoanalytical reference, this essay investigates the impasses experienced by mothers who were welcomed and assisted by the author of the research, and from the discourse of this mothers covers the subjective and social factors that permeated domestic violence relationship committed by their children. So, it was part of the theoretical path, recording some of the teachings of violence and aggression in psychoanalysis and present the insertion scenario of Public Policies for Women, which also includes mothers. As research methodology, knowing that the construction of knowledge in psychoanalysis is inseparable from clinical practice, clinical interviews psychoanalytic were elected as a method, supported by the rapid therapeutic effects highlighted by psychoanalysis. From six fragments extracted from clinical interviews with these mothers, it can be concluded that these mothers called not only a law that mediate the relationship between them and their children, but to report their child also denounced something called "mother's desire" pointing to how imperative it was to mark the desire of each stamped on that child abuser. To make a complaint about violence, marked motherhood as central to engendering the family conflict. Thus, the six cases fragments depicted in this research show many paths trodden by these women about motherhood, which permeated by violence of their children, took them as a cause